Avaliação da atividade eletromiográfica dos músculos mastigatórios nos diferentes tipos faciais - Miranda, André Luis Ribeiro de [UNIFESP] (2009)
The purpose of this study was to examine the electromyographic activities of the masticatory muscles in the different facial types. Forty-seven young and adult, 20 being male (42.6%) and 27 females (57.4%), with aged between 17 and 53 years (mean age 25,9 years) was evaluated. All subjects were students, professors or employees of the College of Dentistry and the Course of After-Graduation in Orthodontics of the Methodist University of São Paulo, all of them had permanent dentition, no missing teeth and sound dental occlusion. Not been included in this study, subjects that had submitted at orthognathic surgery, or with any temporomandibular joint disorders and abnormal functional habit, as: nocturnal dental clenching or bruxism. The electromyographic of surface of the masticatory muscles (anterior temporal, masseter and anterior digastric) was carried out of the left side and the right, during the rest, the clenching with maximum voluntary occlusal force and the chewing, in different facial types. The sample was classified into five groups according with Morphological Facial Rate (Ávila, 1958), as: hipereuriprosopo, euriprosopo, mesoprosopo, leptoprosopo and hiperleptoprosopo. The results obtained of this research show that the right anterior temporal muscle during the chewing presented statistical significant difference between the euriprosopo and hiperleptoprosopo facial types; that the left masseter muscle during the clenching presented statistical significant difference between the hiperleptoprosopo and the euriprosopo, mesoprosopo and leptoprosopo facial types; that the right masseter muscle during the rest presented statistical significant difference between the hipereuriprosopo and leptoprosopo facial types in relation to mesoprósopo. In the clenching there was difference between hiperleptoprosopo and the others facial types; and that the muscles: left anterior temporal and both digastrics had not presented statistical significant differences between the different facial types. The analysis of the gotten results allowed to conclude that the higher average during the rest had occurred more frequent in hiperleptoprosopos and leptoprosopos subjects; and during the clenching the higher average had been more frequent in the hiperleptoprosopos subjects and that during the chewing the higher average had occurred more frequently in the hiperleptoprosopos and leptoprosopos subjects.